OPTIMASI PENGELOLAAN ASET PADA PT CLADTEK BI-METAL MANUFACTURING BATAM - Kurniawan, Fadhlika; Prakasa hasibuan, Rizki (LPPM Universitas Putera Batam, 2023)
Asset management has been running so far, but has not been implemented as expected to achieve maximum results. Asset management at PT. Cladtek Bi-Metal Manufacturing Batam still uses the Microsoft Excel application so that problems are encountered in managing assets such as number writing errors, no direct asset report notification, no history of data changes, unable to display data as a whole. The purpose of this research is to find out how to optimize assets and determine the appropriate asset management application for PT. Cladtek Bi-Metal Manufacturing Batam. The selection of asset management applications uses the AHP (Analitycal Hierarchy Process) method with the criteria of Multi User, Help Desk, Log Activity and Design, the priority weight of the criteria for the first rank is 0.405 in the Activity Log, the second rank is 0.372 Multi User, the third rank is 0.119 Help Desk, the fourth rank is 0.104 design. The highest Multi User criteria is on the Snipe IT alternative, the highest Help Desk criteria is on the TALENTA alternative, the highest Log Activity criteria is on the AssetTiger alternative, the highest Design criteria is on the ITDB alternative. The priority alternative is ranked first with a total score of 3.61 on Snipe IT, ranked second 2,947 AssetTiger, ranked third 2,631 ITDB, ranked fourth 1.58 TALENTA.